Development of an Exoskeleton for Ankle and Knee Rehabilitation - López, R.; Torres, J.; Salazar, S.; Lózano, R. (Revista Mexicana de Ingenieria Biomedica, 2014)
Exoskeletons are electro-mechanical systems coupled to the body limbs focused mainly in increasing strength, speed and performance. The main applications are in the military, industry, and medicine, particularly used for the rehabilitation of the extremities. In this paper, we presented an exoskeleton with two degrees of freedom for rehabilitation of ankle and knee. The design and construction are based on the instrumentation and control of right lower limb orthoses. The Exoskeleton uses sensors that estimate the force produced by the human, these sensors are coupled in the SEA (Series Elastic Actuator) used for amplifying human strength. The strength amplification can be increased or decreased as needed, allowing the user an evolutionary improvement to reach rehabilitation. The exoskeleton has sensors for estimated angular position and angular velocity of joints, which are used to control the leg movement. The goal is to design a low-cost exoskeleton that provides a reduction in the effort required by the user to remain in a standing position and to do some static rehabilitation exercises such as flexion and extension of the legs.